STRATEGI KEMITRAAN SEKOLAH DENGAN DUNIA INDUSTRI DALAM MENDUKUNG PENDIDIKAN VOKASI DI SMK NEGERI 7 PEKANBARU - Syahrani Selian, Alfia; Hayu Pratiwi, Salsa; Gupron, Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Partnerships between schools and the industrial sector are an important strategy in supporting the implementation of vocational education that is relevant to the needs of the workforce. Effectively managed partnerships can improve students’ competencies through various collaborative programs with the industrial sector. This study aims to describe the strategy of school partnerships with the industrial sector in supporting vocational education at SMK Negeri 7 Pekanbaru and to identify the supporting and inhibiting factors in its implementation. This study employed a qualitative approach with a descriptive research design. The research informants consisted of the Vice Principal for Public Relations, the Principal, Heads of Expertise Programs, and representatives from industrial partners. Data were collected through interviews, observations, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results showed that the school partnership strategy was implemented through three stages: strategy formulation, strategy implementation, and strategy evaluation. Strategy formulation was carried out through identifying industrial needs, internal coordination, and the preparation of Memorandums of Understanding (MoU) and Cooperation Agreements (PKS). Strategy implementation was realized through programs such as Industrial Work Practice (PKL), guest teachers, teacher internships, Teaching Factory (TeFa), seminars, training, and graduate placement. Evaluation was conducted through monitoring, communication with industrial partners, and discussions on program implementation results. The success of the strategy was supported by the commitment of the school community, leadership support, and effective communication with industrial partners, while the obstacles included limited PKL placement capacity, communication constraints, and student discipline issues. A well-planned and sustainable partnership strategy is able to support vocational education at SMK Negeri 7 Pekanbaru.